Cover Image. Issue 2 (25th February 2019) - Matsuzaki, Shinya; Kakigano, Aiko; Mimura, Kazuya; Nagase, Yoshikazu; Endo, Masayuki; Kimura, Tadashi
Abstract : The cover image is based on the Clinical Image Gross image of vasa previa restored in the postpartum period by Shinya Matsuzaki et al., DOI:10.1002/ccr3.2067 .